IMPROVING STUDENTS’ PARTICIPATION IN SPEAKING CLASS THROUGH ROLE PLAY (The Case at Grade XI of State Senior High School 1 Pemalang in the Academic Year of 2012/2013) (English Education Journal, 2013)
The objective of this research is to improve students’ participation in speaking class through the role play technique. The researcher employed collaborative classroom action research design. The research was conducted in a single class consisting of thirty six students. The procedure of the research consists of four main steps: planning, implementation, observation and reflection. To collect the data, he used some instruments i.e. observation checklist, questionnaire, and test. After the data were collected, the researcher analyzed them. The findings of this research showed that the students' participation improved from one cycle to the following cycle. This can be seen from the result of each cycle. The students’ participation in pre-cycle was poor, in the first cycle was fair and in the second cycle was good. The students’s speaking ability also  increased from one cycle to the following cycle. This can be seen from the mean of students’ speaking ability in pre-cycle was 75, in the first cycle was 79 and in the second cycle was 83. From the result of the research showed that the students actively participated in speaking class, their speaking ability was better and the teacher can implement the teaching technique appropriately.